Collaborative lesson design of acid base titration curve in Indonesia senior high school - M Amzar; S Hendayana; W Wahyu; A Supriatna; S Lestiyani (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Acid base titration curve is one of the important topics in Indonesia senior high schoolchemistry. Base on interview with chemistry teachers from different province, the study revealedmost of the teachers disregarded this topic, because they got difficulties to find the best strategy to teach the topic effectively and efficiently. The purpose of this study is to develop acollaborative lesson design based on sharing and jumping task of acid base titration curve at thesenior high school level in Indonesia. The topic of acid base titration curve can promote highorder thinking skills of the student how to present and to communicate data of acid base titration.The methodology used is didactical design research (DDR). Didactical design research has treesteps are, (a) analyzing didactical condition before learning, (b) analyzing metapedadidacticaland (c) analyzing retrospective. Data were collected by interview teacher from differentprovinces, recordings (audio). The lesson design has been develop, include learning target,prediction student response, and teacher assistance. The developed lesson design will beimplemented at grade 11 of senior high school in Bandung.